HUBUNGAN PENGETAHUAN DAN SIKAP IBU BALITA DENGAN KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) DI PUSAT KESEHATAN MASYARAKAT OEBOBO TAHUN 2016 - RIRIN WIDYASTUTI (JURNAL INFO KESEHATAN, 2016)
Background: Immunization is very important to prevent the occurrence of certain diseases in a person, a group of people (population) or even eliminate certain diseases in the world. Long-term immunization programs in Indonesia have recently faced obstacles with an unreliable information about immunizations that many parents hesitate and fear to immunize their babies. Improper information often uses the issue of fear (fear mongering) on Post-Immunization Follow-Up Events (KIPI) that may occur to a child after getting immunized. KIPI or adverse events following immunization (AEFI) is a medical event that is suspected to be associated with immunization, either in the form of vaccine reactions or adverse effects, pharmacological effects, injection reactions or procedural errors. Problem Formulation: How is the Relationship of Knowledge and Attitudes of Underfives with Follow Up Immunization (KIPI) at Oebobo Public Health Center in 2016 ?. Research Objectives: To know the relationship between knowledge and attitude of Mother and Toddler with KIPI at Oebobo Public Health Center in 2016. Method: This research type is analytic survey research using cross-sectional research design. The population in this research is all mother of toddler (0-59 month) in work area of health center Oebobo which amounted to 348 people. The sampling technique by accidental sampling that fulfill the inclusion and exclusion criteria is 80 people. Technique of collecting data by using questionnaire. Data analysis technique using univariate analysis in the form of frequency distribution table and bivariate with Chi-Square. Result: Frequency distribution of children affected by KIPI 52 people (65%) with mild reaction 45 cases (86.5%), respondents knowledge about KIPI is good 29 respondents (36.25%). The positive attitude of the mother of baby equal to 68 respondents (85%). There is relationship between knowledge of mother of toddler with KIPI (p-value: 0.038) and there is no relation between mother attitude of toddler with KIPI (p-value: 0.744). Conclusion: There is a correlation between knowledge and attitude of mother under five with KIPI at Oebobo Public Health Center in 2016.